Bacterial lipid diversity - López-Lara, Isabel M.; Geiger, Otto (Biochimica et biophysica acta. Molecular and cell biology of lipids, 2017)
The glycerophospholipids phosphatidylethanolamine, phosphatidylglycerol (PG), and cardiolipin (CL) are major structural components of bacterial membranes. In some bacteria, phosphatidylcholine or phosphatidylinositol and its derivatives form part of the membrane. PG or CL can be modified with the amino acid residues lysine, alanine, or arginine. Diacylglycerol is the lipid anchor from which syntheses of phosphorus-free glycerolipids, such as glycolipids, sulfolipids, or homoserine-derived lipids initiate. Many membrane lipids are subject to turnover and some of them are recycled. Other lipids associated with the membrane include isoprenoids and their derivatives such as hopanoids. Ornithine-containing lipids are widespread in Bacteria but absent in Archaea and Eukarya. Some lipids are probably associated exclusively with the outer membrane of many bacteria, i.e. lipopolysaccharides, sphingolipids, or sulfonolipids. For certain specialized membrane functions, specific lipid structures might be required. Upon cyst formation in Azotobacter vinelandii, phenolic lipids are accumulated in the membrane. Anammox bacteria contain ladderane lipids in the membrane surrounding the anammoxosome organelle, presumably to impede the passage of highly toxic compounds generated during the anammox reaction. Considering that present knowledge on bacterial lipids was obtained from only a few bacterial species, we are probably only starting to unravel the full scale of lipid diversity in bacteria. This article is part of a Special Issue entitled: Bacterial Lipids edited by Russell E. Bishop. •Bacterial lipid diversity is immense and so far scarcely explored.•For the synthesis of a specific lipid, distinct pathways may be employed by different bacteria.•Ornithine lipids display high head group diversity.•Phenol or ladderane lipids endow membranes with special properties.